Studies on the environmental and genetic parameters for lamb survival, growth and wool traits of the Elsenburg Dormer and SA Mutton Merino flocks - Muller, Anieka (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.